Cooperative Group-Based Speech Writing Training Investigation on Student Class VI SD Pulibuah Districts Raya Kahean - Mery Chris Isabella Saragih (IJCS: International Journal of Community Service, 2022)
Speech is a activity speak in front general or give a speech for express his opinion, or give an idea about something. Speech usually brought by a which give orations and statement about something things/events that are important and worthy of discussion. Speech is one of the theories of lesson language indonesian . See condition child in time now, more consequence progress technology like smartphone, it is very rare that there is direct communication between one another In real life, everyone is busy with communicating in cyberspace. When again time for them to practice speaking face to face with the other person? Reflecting on In this case, we are motivated to do service to students in order to go through In this they practice speaking formally/officially as well as train critical thinking. Because from an early age, students trained so that they are able to communicate, convince listeners against argument delivered. Result student more brave communicate with good in life daily more on situation official because communicate is wrong one capital for reach success in time front.